Appearance, consumer liking and preferences of Lucanian 'Soppressata' salami. (September 2020) - Napolitano, Fabio; Girolami, Antonio; Faraone, Daniela; Chaudry, Muhammad Mudassir Arif; Braghieri, Ada
Abstract: We assessed the effect of the raw material origin and preservative on the appearance and consumer liking of Soppressata salami to give information concerning the best process conditions to fulfil consumer needs. The effect of visible fat ratio on consumers' acceptability and preference was also evaluated. Image analysis based on Computer Vision System showed that Soppressata cured with nitrites had higher levels of red, yellow, hue and chroma, whereas its fat showed higher levels of lightness, redness, and lower levels of hue. Consumers liked more cured Soppressata, made by using pork cuts and fat from pigs bred on plants using growth-to-finish systems and transformed on site as compared with products obtained by using raw material bought from the market. Most of the consumers considered acceptable the slices with lower visible fat ratio (8.28–17.98%). Therefore, a visible fat ratio below 18%, the use of internal meats and added nitrates appear to be the best process conditions to fulfil consumer needs. Highlights: We used Soppressata made with or without nitrates. Soppressata was made with meat from pigs reared on site or bought from the market. Computer Vision System discriminated the color changes due to nitrite use. Soppressata made with meat from pigs reared on site and added nitrates was preferred. Consumers considered more acceptable slices with lower visible fat ratios.